On the discontinuity of the future by other means: reviewing the foresight world of Richard Slaughter - Mendonça, S. (Futures, 2017)
Richard Slaughter has made pioneering contributions to futures research. These contributions have been both procedural and substantive. This review seeks to appreciate some of the progress that his work has brought to the field through a review of two of Slaughter’s most recent books The Biggest Wake-up Call in History (2010) and To See with Fresh Eyes (2012). This paper traces how Slaughter’s intellectual wake-up built up over time. It highlights a set of fundamental tools, ideas and ideals that spring from Slaughter’s work over decades and is synthesised in these two books. This appraisal becomes an “augmented review” by also taking into account his book blurb material and peer-reviewed journal work. This review draws on this evidence to analyse and profile the multi-disciplinary resonance of these references and to illustrate the broader intellectual impact. In addition a bibliometric analysis offers a way beyond the two books and performs an out-of-sample assessment of the way Slaughter has continued to develop the foresight agenda.